(untitled) (Research, Society and Development, 2025)
The objective of this study was to investigate the relationship between physical activity and mental health in individuals over 40 years old living in Aracaju, Sergipe. This is an exploratory, cross-sectional, and quantitative study conducted with participants recruited from gyms, public exercise programs, and hydro-gymnastics centers. Mental health was assessed using the Self-Reporting Questionnaire (SRQ-20), and sociodemographic and exercise practice data were collected through structured questionnaires. A total of 124 individuals were analyzed, mostly female (73%), with an average age below 60 years and an income below five minimum wages (44%). Among the participants, 12.9% showed mental distress (SRQ-20 ≥ 7), which was more frequent in women, individuals with lower income, and those who did not engage in weight training, Pilates, or hydro-gymnastics. No statistically significant difference in mental health was observed among the exercise modalities; however, individuals who did not practice any of these activities showed significantly higher levels of psychological distress (p < 0.001). Additionally, participants with mental distress reported higher use of psychotropic drugs and a greater perceived need for psychotherapy. It is concluded that although no specific exercise modality proved superior in promoting mental health, physical activity in general was associated with lower levels of psychological distress, reinforcing its importance as a strategy to promote mental well-being in adults and the elderly.